Study on Population Growth of Big Cities in Sumatra Island - IB Ilham Malik (Jurnal Arsitektur, 2022)
The population of the city will continue to increase without control because there is no population determination policy. The spatial plan document does not stipulate the capacity of city residents. As a result, there has been an expansion of land use which has created environmental problems and there has been a regular increase in urban infrastructure to serve an unplanned population growth. This study aims to determine the population growth in the provincial capital city on the island of Sumatra. It is known that in 2010 there were two metropolitan cities, but in 2020 there were three metropolitan cities in Sumatra. It is estimated that by 2030 there will be five metropolitan cities. Within 10 years, Bengkulu City has had a population growth of up to 87%. The population in 6 cities in Sumatra grew below 25% and 3 cities grew above 25% with a total population increase of up to 1.3 million people in one decade.